1995
DOI: 10.1063/1.555963
|View full text |Cite
|
Sign up to set email alerts
|

Standard Reference Data for the Thermal Conductivity of Water

Abstract: New experimental data on the thermal conductivity of liquid water along the saturation line have been obtained recently, using the bare and coated transient hot wire technique, with high accuracy. The quality of the data is such that new standard reference values can be proposed with confidence limits of 0.7% at a 95% confidence level. These data and the correlation herein presented revise a previous correlation endorsed by IUPAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
198
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(219 citation statements)
references
References 0 publications
17
198
0
4
Order By: Relevance
“…The thermal conductivity of the water increased for a reaction temperature below 100 C (Ramires et al, 1995), and maintained a constant value at the reaction temperature from 100 to 150 C while decreasing at temperatures above 150 C. Although the thermal conductivity of the dewatered sludge showed a low value of 0.230 W/mÁ C at the initial stage, as shown in Figure 4b, the thermal conductivity increased rapidly from 130 C as the bound water changed into free water. The thermal conductivity of sludge was 0.704 W/mÁ C, which was 4% higher than that of the water when the dewatered sludge changed into liquid slurry as shown in Figure 2g, due to the thermal hydrolysis reaction above 200 C.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The thermal conductivity of the water increased for a reaction temperature below 100 C (Ramires et al, 1995), and maintained a constant value at the reaction temperature from 100 to 150 C while decreasing at temperatures above 150 C. Although the thermal conductivity of the dewatered sludge showed a low value of 0.230 W/mÁ C at the initial stage, as shown in Figure 4b, the thermal conductivity increased rapidly from 130 C as the bound water changed into free water. The thermal conductivity of sludge was 0.704 W/mÁ C, which was 4% higher than that of the water when the dewatered sludge changed into liquid slurry as shown in Figure 2g, due to the thermal hydrolysis reaction above 200 C.…”
Section: Resultsmentioning
confidence: 97%
“…In Figure 5, thermal conductivity of water is the reported value (Kirillov, 2006;Ramires et al, 1995), and the thermal conductivity of sludge was determined using eq 3 with the temperature difference value from Figure 4a. Heat transfer was accomplished by conduction (not by convection) because a convection resister plate was installed in the reaction container.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on Eq. (4), it can be found that the convective heat transfer coefficient (α f ) is only affected by the water thermal conductivity and increases roughly by 7% as the temperature rises from 40 to 70 ºC [16]. However, the flux at 70 ºC was 2.8 times of the flux at 40 ºC.…”
Section: Influence Of Module Design On Vmd Performancementioning
confidence: 98%
“…Figure 11 shows the thermal conductivity of nanolubricants measured in comparison to those of water and 10 wt% glycerol. It is observed that water presents the highest thermal conductivity among all the liquids, showing a value of around 0.6 W/mK at an ambient temperature of 23 °C [31]. A possible reason is that a concentration of 10 wt% glycerol has very low thermal conductivity (0.29 W/mK) [32], which may greatly lower down the thermal conductivity of water-based solutions.…”
Section: Grain Refinement Mechanismmentioning
confidence: 99%